Emotion Regulation and Attitudes Toward Conflict in Colombia: Effects of Reappraisal Training on Negative Emotions and Support for Conciliatory and Aggressive Statements - Hurtado-Parrado, Camilo; Sierra-Puentes, Myriam; El Hazzouri, Mohammed; Morales, Alexandra; Gutiérrez-Villamarín, Diana; Velásquez, Laura; Correa-Chica, Andrea; Rincón, Juan Carlos; Henao, Karen; Castañeda, Juan Gabriel; López-López, Wilson (Frontiers in Psychology, 2019)
Control of negative emotions (e.g., anger and fear) by political cues perpetuate intractable conflict by mobilizing public support for aggressive actions. Halperin et al. (2013) found that reappraisal – an adaptive form of emotion regulation – decreased negative emotions triggered by anger-inducing information related to the Israeli-Palestinian conflict, and increased support for conciliatory statements. We tested these effects in the context of the conflict between the Colombian government and the Fuerzas Armadas Revolucionarias de Colombia (FARC-EP). Reappraisal training reduced negative emotions produced by a presentation that illustrated FARC’s violent actions, and increased support for conciliatory statements (with overall moderate effect magnitudes). We also found that negative emotions mediated the effects of reappraisal on the support for aggressive and conciliatory statements. These findings indicate a high degree of generality of the phenomena, especially considering the differences between the Israeli-Palestinian and Colombian conflict; also, show promise for replicating these effects on other types of intergroup conflicts and guiding effective public policy.